Pengaruh Takaran Pupuk Kascing dan Pupuk Majemuk terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays-saccharata Sturt) - Ludovikus Karisma Sabu; Zamroni; Darnawi (Universitas Sarjanawiyata Tamansiswa, 2022)
The research which aims to determine the effect of dose of vermicompost and NPK fertilizers on the growth and yield of sweet corn (Zea mays-saccharata Sturt) has been carried out at the Pusat Pelatihan Pertanian dan Pedesaan Swadaya (P4S) “Lestari Makmur”, located at Jalan Wates Km. 12, Semampir Hamlet, Argorejo Village, Sedayu District, Bantul Regency, Yogyakarta Special Region in January-April 2022. This study used a Completely Randomized Block Design (RCBD) with a 3x3+1 factorial pattern consisting of 3 replications. The first factor is the dose of vermicompost fertilizer which consists of 3 levels, namely: 2 tons/ha (K1), 4 tons/ha (K2), and 6 tons/ha (K3). The second factor is the dose of NPK fertilizer which consists of 3 levels, namely: 200 kg/ha (N1), 250 kg/ha (N2), and 300 kg/ha (N3) in order to obtain 9 treatment combinations plus 1 control treatment, namely K0N0 (without fertilizer). The observed variables were plant height, stem diameter, plant fresh weight, dry weight of plant, length of ear, diameter of ear, weight of ear per plant, and weight of ear per hectare. Data were analyzed using variance followed by Duncan's Multiple Range Test (DMRT) at 5% level. The results showed that there was no interaction between doses of vermicompost and NPK fertilizers on plant growth and yield, except for stem diameter and fresh weight of sweet corn. The treatment doses of vermicompost and NPK were significantly different and higher than the control (without fertilizer) both on growth and yield variables. The dose treatment of vermicompost and NPK fertilizer did not have a significant effect on the growth variables (dry weight of plants) and yield (cob weight per hectare) of sweet corn.